Swarm in a Fly Bottle: Feedback-Based Analysis of Self-organizing Temporary Lock-ins - Hamann, Heiko; Valentini, Gabriele (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Generating EAST-ADL Event Chains from Scenario-Based Requirements Specifications - Koch, Thorsten; Holtmann, Jörg; DeAntoni, Julien (Software Architecture)
Real-time software-intensive embedded systems complexity, as in the automotive domain, requires rigorous Requirements Engineering (RE) approaches. Scenario-based RE formalisms like Modal Sequence Diagrams (MSDs) enable an intuitive specication and the simulative validation of functional requirements. However, the dependencies between events occurring in different MSD scenarios are implicit so that it is difficult to find causes of requirements defects, if any. The automotive architecture description language EAST-ADL addresses this problem by relying on event chains, which make dependencies between events explicit. However, EAST-ADL event chains have a low abstraction level, and their relationship to functional requirements has seldom been investigated. Based on the EAST-ADL functional architecture, we propose to use its central notion of event to conciliate both approaches. We conceived an automatic transformation from the high abstraction level requirements specified in MSDs to the low abstraction level event chains.

Use Your Best Device! Enabling Device Changes at Runtime - Bokermann, Dennis; Gerth, Christian; Engels, Gregor (12th International Conference on Business Process Management (BPM 2014))

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013

Efficient XML Keyword Search Based on DAG-Compression - Böttcher, Stefan; Hartel, Rita; Rabe, Jonathan (Database and Expert Systems Applications - 25th International Conference, DEXA 2014)

Fast Collisionless Pattern Formation by Anonymous, Position-Aware Robots - Lukovszki, Tamás; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Continuous Aggregation in Dynamic Ad-Hoc Networks - Abshoff, Sebastian; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Aggregation of Network Protocol Data Near Its Source - Fourné, Marcel; Stegemann, Kevin; Petersen, Dominique; Pohlmann, Norbert (Information and Communication Technology)

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

A Taxonomy-Based Approach towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard (Distributed, Ambient, and Pervasive Interactions)